Public Harmonization in Organizing the Rule of Law Democratic Party - Sacipto, Rian; Ciptono, Ciptono (Law Research Review Quarterly, 2018)
Problems and violations of the course of the implementation of the democratic party in the Indonesian law state, of course, have become a matter of great concern. Where the community began to fret and uncomfortable about the problems caused by some groups or persons with the intention to damage, incite and create a ruckus even do everything they can to disrupt the process of carrying out the democratic party. Harmonization is a natural sense in carrying out harmony or one form of effort in producing something sublime unity. This paper provides a positive study based on normative theories and methods of drawing conclusions from general matters to specific matters. Where the harmonization of the public must be created and carried out in organizing the democratic party to avoid things that can damage the unity of the nation and the occurrence of all forms of violations and criminal acts in the course of the democratic party of the rule of law of Indonesia. To realize this, where all components in the continuation of the implementation of the democratic party, it is expected that all the people, prospective participants or contestants in the election and state institutions that have received the mandate from the government must create and create a democratic party atmosphere that is consistent with election principles and regulated in Chapter 2 Article 2 of Law No.7 of 2017.